Prominence and consumer search - Armstrong, M; Vickers, J; Zhou, J (University of Oxford, 2008)
This paper examines the implications of "prominence" in search markets. We model prominence by supposing that the prominent firm will be sampled first by all consumers. If there are no systematic quality differences among firms, we find that the prominent firm will charge a lower price than its non-prominent rivals. The impact of making a firm prominent is that it will typically lead to higher industry profit but lower consumer surplus and welfare. The model is extended by introducing heterogeneous product qualities, in which case the firm with the highest-quality product has the greatest incentive to become prominent, and making it prominent will boost industry profit, consumer surplus and welfare.